An Experimental Study on External Ventilation to the Heating Performance of Household Air Source Heat Pump - Zou, Hang; Liu, Zhanqiang; Long, Enshen (Frontiers in Energy Research, 2021)
The external ventilation conditions have a great influence on the heating performance of the air source heat pump (ASHP) systems. The outdoor units of residential household air source heat pumps are often installed in narrow spaces such as balconies. The ventilation conditions of the outdoor unit will influent the heating performance of the air source heat pump. It is necessary to study the effect of the outdoor unit ventilation conditions on the heating performance of residential household heat pumps. This paper experimentally studied the heating performances of an air source heat pump system with the outdoor unit mounted in a balcony in different external ventilation conditions. The results indicate that the ventilation conditions for the outdoor units have a significant effect on the heating performance of the system. When the inlet of the outdoor unit was close to the sliding door and completely blocked, the ventilation environment was the worst and the coefficient of performance (COP) was the lowest. In addition, the unfavorable ventilation environment could result in a reduction of the COP by 26.2%. When the inlet of the outdoor unit was partially blocked, the heating performance could be improved and the COP was also slightly improved. The great heating performance was obtained under the cross-ventilation condition. This paper can guide the design of the installation position of the household air source heat pump outdoor units in actual engineering.